Answer:
[tex]\displaystyle T_6=\frac{448}{729} f^2t^6[/tex]
Step-by-step explanation:
Binomial Theorem
Any power of x + y can be expanded into a sum of the form:
[tex]\displaystyle (x+y)^{n}={n \choose 0}x^{n}y^{0}+{n \choose 1}x^{n-1}y^{1}+{n \choose 2}x^{n-2}y^{2}+\cdots +{n \choose n-1}x^{1}y^{n-1}+{n \choose n}x^{0}y^{n}[/tex]
For any given term k, counted from 0 to n:
[tex]\displaystyle T_k={n \choose k}x^{n-k}y^{k}[/tex]
Note if we have to find the 7th term, we have to use k=6. The expression is:
[tex]\displaystyle \left(4f+\frac{t}{3}\right)^8[/tex]
For n=8, x=4f, y=t/3, k=6:
[tex]\displaystyle T_6={8 \choose 6}(4f)^{8-6}\left (\frac{t}{3} \right )^{6}[/tex]
[tex]\displaystyle T_6={8 \choose 6}(4f)^{2}\left (\frac{t}{3} \right )^{6}[/tex]
[tex]\displaystyle T_6={8 \choose 6}16f^2\frac{t^6}{3^6}[/tex]
Calculate:
[tex]\displaystyle {8 \choose 6}=\frac{8!}{2!\cdot 6!}=28[/tex]
Thus:
[tex]\displaystyle T_6=28\cdot 16f^2\frac{t^6}{729}[/tex]
Simplifying, the 7th term is:
[tex]\mathbf{\displaystyle T_6=\frac{448}{729} f^2t^6}[/tex]